HUBUNGAN HIPERTENSI TERHADAP TEKANAN INTRAOKULER PADA PASIEN RS PRIMA JAMBI - Roni Linson Girsang (Nightingale: Journal of Nursing, 2024)
Hypertension is a common condition found in the community and can affect various organs, including the eyes. Increased intraocular pressure (IOP) can lead to vision problems, such as glaucoma, which may result in blindness if not properly managed. This study aims to analyze the relationship between hypertension and intraocular pressure in patients treated at RS Prima Jambi. A cross-sectional design was used with a sample of hypertensive patients undergoing eye examinations at RS Prima Jambi. Blood pressure and intraocular pressure measurements were taken using standard medical equipment. The data obtained were analyzed using statistical tests to examine the correlation between the two variables. The results of this study are expected to provide clearer information about the impact of hypertension on increased intraocular pressure, which can serve as a basis for better eye health management in hypertensive patients. This research is expected to contribute to the prevention and early detection of eye disorders in hypertensive patients in Indonesia.